Diagnosis Toksoplasmosis Kongenital Berdasarkan Gen Surface Antigen-1 Toxoplama gondii Isolat Lokal Menggunakan Polymerase Chain Reaction (DIAGNOSIS OF CONGENITAL TOXOPLASMOSIS BASED ON SURFACE ANTIGEN -1 GENE OF LOCAL ISOLATE TOXOPLASMA GONDII USING POLY - Priyowidodo, Dwi; Hartati, Sri; Kusumawati, Asmarani; Prastowo, Joko (Jurnal Veteriner, 2015)
Congenital toxoplasmosis has an important role in the transmission of toxoplasmosis in animals andhumans. Thus, a rapid and an accurate diagnostic method is needed. The aim of this study was to conductthe diagnosis technique of congenital toxoplasmosis in mice based on surface antigen-1 (SAG-1) gene oflocal isolates (IS-1) T. gondii using Polymerase Chain Reaction (PCR). A total of 15 pregnant mice Balb/C strain with the aged of eight weeks were used as experimental animal. Mice were intraperitoneallyinfected with 103tachizoit of T. gondii RH strain at day 9th of gestation. Amniotic fluids, blood, fetus, andplacenta then were collected at day 1, 2 , 3, 4 and 5 post infection. DNA was extracted from the abovesamples using PureLinkTM Genomic DNA Kit (Invitrogen, Life Technologies, US), and then amplified byusing specific primer based on SAG-1 gene of the local isolate T. gondii. This study shows that positivePCR result were seen in all samples of amniotic fluids at day 2 up to day 5 post infection. Fetus andplacenta samples also show positive PCR result at 3 up to day 5 post infection. Negative PCR result showsin blood samples, however. To conclude, PCR technique using SAG-1 gene of local isolates T. gondii as atarget gene, could be used to detect congenital toxoplasmosis from infected mouse samples such as, amnionfluids, fetus, and placenta. Further research was needed to apply the PCR method with SAG-1 gene of localisolate T. gondiion the human samples of congenital toxoplasmosis.
Keywords: congenital toxoplasmosis, polymerase chain reaction (PCR), SAG-1 gene of T. gondii